Edukasi Pencegahan KDRT Kepada Masyarakat Desa Wonoharjo - Fernando Fernando; Apria Ningsih; Sazirman Sazirman; Yanuar Irfan Karami; Yolan Rama Dandi; Nur Cholipah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Domestic violence (DV) remains a persistent social issue that requires serious attention, particularly in rural areas like Wonoharjo Village. This community service program aimed to enhance the understanding and awareness of the community regarding DV prevention through a series of educational activities, conflict resolution training, and group discussions. A participatory approach was employed to actively involve the community in each stage of the program. The results demonstrated a significant improvement in the knowledge and skills of the community concerning DV prevention. Furthermore, the formation of community task forces and the emergence of local leaders served as key indicators of social change. This program successfully raised collective awareness about gender equality and women's rights in the village. The recommendation is to continue education and support programs to ensure sustainable prevention of domestic violence.